Understanding the rice domestication concepts by experimenting with traditional rice varieties: Understanding the rice domestication concepts - R. D, Vijaya Lakshmi; Sathiya Priya , Kamatchi; Fathima , Junaitha; Mahadevan , Aparna; Senthil Kumar, Muthu Rakku; Krishnamoorthi, Akash; Madhavan, Madheswaran; karthikeyan, veluswamy (ORYZA-An International Journal of Rice, 2025)
India conserves remarkable insights of domestication of wild rice into cultivated rice. Throughout the world the rice domestication and evolution of rice is a complex research. Many reports are evolving every day to prove the rice domestication. Our present study also aims towards the rice domestication by studying the characteristic features of Traditional Rice Varieties (TRVs) of Tamil Nadu which includes unexploited the mother gene pool. The selected varieties includes Kala Namac (Oryza sativa), Karuppu Kavuni (Oryza rufipogon), Karung Kuruvai (Oryza rufipogon), Nocora (Oryza sativa), Garudan Samba (Oryza sativa), compared with cultivated oneslike Authur Samba (Oryza sativa), Salem Senna (Oryza sativa), 13 Bt (Oryza sativa) resulted how the Culm, Ligules, Panicles, Panicles Length, No of Tillers, No of Spikelet per panicle, Plant Height, seed weight, Length &Breadth ratio, Seed shattering habit that influenced the domestication of wild rice into cultivated rice. The wild rice Oryza rufipogon stand as a mother to domesticated rice Oryza sativa. This proven concept have been re-examined by with our Traditional Rive Varities. present study.